2016
DOI: 10.1590/1516-4446-2014-1574
|View full text |Cite
|
Sign up to set email alerts
|

High-risk behaviors and experiences with traffic law among night drivers in Curitiba, Brazil

Abstract: Objective: To explore high-risk behaviors and experiences with traffic law among night drivers in Curitiba, Brazil. Method: Data from 398 drivers on sociodemographic parameters, high-risk behaviors, experiences with traffic law, and traffic law violations were collected through interviews conducted at sobriety checkpoints. Exploratory-descriptive and analytical statistics were used. Results: The mean age of the participants was 32.6611.2 years (range, 18 to 75 years). Half of the drivers reported having driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…Some studies have shown that single people adopt more risky behaviors (e.g., excessive speed and DUIA) than those who are married [18,50,51]. Similarly, this study found unmarried status to be a risk factor for DUIA in all Brazil and in the Central-West macroregion.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Some studies have shown that single people adopt more risky behaviors (e.g., excessive speed and DUIA) than those who are married [18,50,51]. Similarly, this study found unmarried status to be a risk factor for DUIA in all Brazil and in the Central-West macroregion.…”
Section: Discussionsupporting
confidence: 73%
“…The independent variables included: (i) sex: Female or male; (ii) age (years): 18-29, 30-39, 40-59, or ≥60 [30]; (iii) self-reported race/skin color: White, black, brown, or others (native Brazilian or Asian); (iv) education level: Illiterate or elementary school incomplete, elementary school complete or high school incomplete, high school complete or college school incomplete, or college school complete or above; (v) marital status: With partner or without partner [18]; (vi) residence area: Within the capital, within of metropolitan regions, or within other regions (residence outside the capital or metropolitan regions); (vii) age at start of alcohol use (years): ≥18 or <18 [15]; (viii) binge drinking in the previous 30 days: No or yes [15]; (ix) tobacco use in the previous 30 days: No or yes; and (ix) depression: No or yes. To account for variation in each macroregion, the state was also considered as an independent variable.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Although there was a nationwide decrease, pedestrians remain the main victims of RTI. Brazil has relatively strong national legislation on key aspects of road safety, but a reasonable doubt emerges about its enforcement, especially related to drinking and driving laws [ 62 , 63 ]. Numbers of motorcyclist road injury deaths increased the most from 1990 to 2015, probably linked to a high rise in the use of this kind of vehicle [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 Some studies have shown that repeat offenders in Brazil are usually aware of the traffic laws and risks of TCs involving specific behaviors, which supports the fact that there is lack of social deterrence among Brazilian drivers. 38 , 39 In our study, 43.3% of drivers with alcohol-related infractions reported they had been stopped at a roadblock in the previous year. Although most said they believed in the effectiveness of enforcement, they were being fined for drinking and driving at the time of data collection.…”
Section: Discussionmentioning
confidence: 50%
“…While there is still no consensus, most studies suggest that social deterrence is an effective way to reduce negative outcomes in traffic 36,37. Some studies have shown that repeat offenders in Brazil are usually aware of the traffic laws and risks of TCs involving specific behaviors, which supports the fact that there is lack of social deterrence among Brazilian drivers 38,39. In our study, 43.3% of drivers with alcohol-related infractions reported they had been stopped at a roadblock in the previous year.…”
mentioning
confidence: 99%